Linkages Between Fiscal Policy and Financial (In)Stability - Mirna Dumičić (Journal of Central Banking Theory and Practice, 2019)
This paper identifies and describes some of the main channels through which fiscal policy is linked to financial stability. For that purpose, several features of public debt related to financial stability are explored, such as public debt management and its sustainability, government's funding costs and their impact on costs of funding for private sector, financial institutions' exposures to the government etc. The part related to the tax policy elaborates on its countercyclical capacity, the role of automatic stabilizers, tax incentives that encourage or discourage certain type of financing, and impact of tax reliefs on systemic risks, particularly those targeted at the real estate. Fiscal policy role during the periods of strong capital inflows is also described from the financial stability point of view, which is followed by the overview of fiscal and quasi-fiscal costs of financial instability.Specific problem of different time horizon of economic policymakers', which is in the case of fiscal policy usually related to election cycles and thus negatively affects its countercyclical capacity, is also explored. Given the relevance of the identified channels for financial stability, it can be expected that macroprudential capacity of fiscal policy will gain much more attention in the future research and policy work.
Keywords: E60; E62; E58; 330; fiscal policy; financial stability macroprudential policy; systemic risks